nandb—number and brightness in R with a novel automatic detrending algorithm - Nolan, Rory (Bioinformatics, 2017)
SUMMARY: An R package for performing number and brightness image analysis, with the implementation of a novel automatic detrending algorithm. AVAILABILITY AND IMPLEMENTATION: Available at https://github.com/rorynolan/nandb for all platforms. CONTACT: rnolan@well.ox.ac.uk or spadilla@well.ox.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.